The patron thief of bread - Eagar, Lindsay (Candlewick Press, 2022)
Fished out of a local river as an infant, eight-year-old Duck has lived a life of petty thievery and hiding from authorities as part of a gang of street urchins known as the Crowns. When gang leader Gnat finds them a permanent home in an unfinished abandoned cathedral, he devises a plan for Duck to apprentice to a local baker, where she'll pilfer food and money for them, allowing them to live in relative comfort. As she begins a life working for the kindly baker Griselde, Duck discovers she has a talent for baking and begins to question her loyalties. Meanwhile, atop the cathedral, a lonely gargoyle longs to fulfill his mission of watching and protecting those in and outside the cathedral.